Development and Evaluation of a Loop-Mediated Isothermal Amplification Assay for Diagnosis of Schistosoma mansoni Infection in Faecal Samples - Ibrahim N. Mwangi; Eric L. Agola; Robert M. Mugambi; Esther A. Shiraho; Gerald M. Mkoji (Journal of Parasitology Research)
Human intestinal schistosomiasis is caused by the blood fluke, Schistosoma mansoni. With intensified efforts to control schistosomiasis by mass drug administration using praziquantel (PZQ), there is an urgent need to have accessible, quality-assured diagnostic tests for case detection and disease surveillance and for monitoring efficacy of treatment and other interventions. Current diagnostic tools are limited by suboptimal sensitivity, slow turn-around-time, affordability, and inability to distinguish current from past infections. We describe a simple and rapid diagnostic assay, based on the loop-mediated isothermal amplification (LAMP) technology for diagnosis of S. mansoni infection in human faecal samples. The LAMP primers used in this assay were previously described and they target a 121-bp DNA repeat sequence in S. mansoni. The LAMP assay was optimized at an isothermal temperature of 63°C for 1 hour. The amplified DNA was either visualized under ultraviolet light after electrophoresis or by directly observing the color change after staining the amplicons with CYBR Green dye. The LAMP assay was evaluated against the microscopy-based procedure and the results were analysed using Cohen’s kappa coefficient to determine the degree of agreement between the two techniques. The LAMP assay reliably detected S. mansoni ova DNA in faecal samples and parasite DNA in amounts as low as 32fg. When the assay was tested for specificity against other faecal-based soil-transmitted helminths (STH), no cross-reactivity was observed. The LAMP assay was superior to the Kato-Katz assay with a 97% specificity; a high positivity score reliably detecting S. mansoni and a Kappa Coefficient of 0.9 suggested an exceptional agreement between the two techniques. The LAMP assay developed has great potential for application in field settings to support S. mansoni control and elimination campaigns.